PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN MOTIVASI BELAJAR MELALUI PEMBELAJARAN BERBASIS MASALAH - Irma Sari Daulay (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2017)
This research aims to know (1) the improvement of mathematical problem solving skill and students’ learning motivation who received problem-based learning and conventional learning, (2) the interaction between learning model and students’ early ability to the mathematical problem solving skill and the students’ learning motivation (3) the completion process of the students’ answers for solving problem on each learning. This research was done in SMP Negeri 4 Padang Bolak. The type of this research used quasi-experimental with pre-test-post-test control group design. The population in this study was all eighth grade students of SMP Negeri 4 Padang Bolak, while the sample was thirty students in VIII-1 class as experimental class and thirty students in VIII-3 class as control class. Sampling is done through random sampling technique. The research instrument used a mathematical problem solving skill test, questionnaire of students’ learning motivation. The hypothesis testing in this study used two way ANOVA test. The result of this study shows that (1) the improvement of the mathematical problem solving skill and the students’ learning motivation who received problem-based learning is higher than conventional learning. The result of the improvement of mathematics problem solving ability which was given problem based learning and the conventional learning was 0,16. It was seen from N-Gain 0,53 to 0,69, while the improvement of students’ learning motivation was 0,15. It was seen from N-Gain 0,17 to 0,32. (2) There is no interaction between learning and students’ mathematical early ability to the mathematical problem solving ability and students’ learning motivation. (3) The completion process of students’ mathematical problem solving answers who are given the problem-based learning is better than the students who are given the conventional learning.